Incorporating evidential reasoning and TOPSIS into group decision-making under uncertainty for handling ship without command - Wu, Bing; Zong, Likang; Yan, Xinping; Guedes Soares, C. (Ocean engineering, 2018)
This paper proposes an improved methodology for handling ships without command by incorporating evidential reasoning and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) in the decision making of emergency responses. The kernel of this method is to use evidential reasoning to integrate the influencing factors expressed by incomplete information of each of the involved organizations, and to employ the TOPSIS method to make the final decision with the asymmetric information distribution among the involved organizations. A ship with main engine failure is considered as the study case to apply the proposed methodology. The result demonstrates that the new method is beneficial for handling ships that are not under command. •An improved methodology for handling ships without command is proposed, incorporating evidential reasoning and TOPSIS.•The kernel is to use evidential reasoning to integrate the influencing factors expressed by incomplete information.•It employs the TOPSIS to make the final decision with the asymmetric information among the involved organizations.•A ship with main engine failure is considered as the study case to apply the proposed methodology.•The result demonstrates that the new method is beneficial for handling ships that are not under command.